Object lessons : lessons learned in object-oriented development projects - Love, Tom (Advances in object technology ;, 1993)
Object Lessons was written to encourage software professionals to build higher quality, yet innovative software products with less risk by avoiding mistakes that plague the industry. The volume focuses on building commercial software products and addresses fundamental issues and trends as opposed to specific products and services. Bringing to the reader over a decade of the author's depth of experience and wisdom in regard to building commercial software products using objects, the volume addresses many questions that technical leaders and managers face as they venture into this important new area of modern software development. The edition supplies valuable insight into the development and management of large-scale commercial software and will prove to be a desirable reference guide for software managers, analysts, designers, implementors, applications programmers, project leaders, and technical managers in the field of object-oriented software engineering.